Pengembangan Kelembagaan Agroindustri Kakao di Sulawesi Tenggara (Studi Kasus pada LEM Sejahtera Tinete di Desa Tinete Kecamatan Aere Kabupaten Kolaka Timur) - Rosmawaty, Rosmawaty; Taufik, Yani (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2018)
This study aims to develop cocoa agroindustry institutions in Southeast Sulawesi Case Study at the Tinete Prosperous Justice LEM in Kolaka Timur District, Aere District, Tinete Village. The study was conducted in June 2014 until June 2015. Determination of the sample is a case study at the Tinete Prosperous Justice LEM in Kolaka Timur District, Aere District, Tinete Village. The method of data collection in this study was carried out by library research methods and field surveys. The institution of cocoa agroindustry was analyzed using descriptive analysis. Respondents for institutional development used five experts consisting of cocoa farmers, the cocoa processing industry (LEM Sejahtera), financial institutions (banking), bureaucratic elements (Regional Government and the Office of Plantation and Horticulture), R & D and Universities. The results showed that LEM Sejahtera needs to build collaboration between members of the Prosperous LEM in the form of a Fermented Cocoa Processing Business Unit in the raw material production center developed in research to address the quality problems of Southeast Sulawesi cocoa. The pattern of institutional linkages as a strategy for agroindustry development is the relationship between farmers, LEM Sejahtera agroindustry management and banking. Farmers as raw material suppliers are also agro-industry players through the management of Prosperous LEM as a productive business group and banks as financial institutions that assist in the capital.